PENDAMPINGAN MANAJEMEN PENGELOLAAN WISATA TRACKING DI DESA CEPAKA KEDIRI TABANAN - I Made Hedy Wartana; AA. Ketut Sri Asih; NLK.Julyanti Paramita (Universitas Triatma Mulya, 2021)
The condition of Cepaka Village is that it is strategically located and surrounded by large expanses of rice fields which have been developed into a tourist village. Because in Cepaka village, several villas have been established which are usually inhabited by foreign guests who want a rural atmosphere and have close access to the coastal area. The existing traking routes have not been optimally utilized so that economically, the existence of the traking routes is not yet visible. This traking route is a potential that requires serious management so that the route can be worked on optimally so that later there will be an economic contribution. Of the problems faced, the solution that can be given is to rearrange the traking properly so that it is more comfortable and beautiful so that the route is more attractive. to be visited and can be offered as a package in traking tours. Another solution offered is traking route management, which can be done by recording the number of tourist accommodations in Cepaka village because the restaurants and villas in Cepaka village can later be invited to collaborate to take advantage of the traking route's facilities which are used as mutually supportive packages. agreement with tourism actors regarding rights and obligations so that the contributions obtained are mutually beneficial, determine the entrance of a centralized trekking so that it can invite the attention of the community for their curiosity, involve the participation of the Cepaka Village community in order to maintain environmental cleanliness for the realization of a beautiful atmosphere in Cepaka village